PENGARUH KESADARAN KELENGKAPAN KEPEMILIKAN SURAT TANDA KENDARAAN BERMOTOR TERHADAP ASPEK TANGGUNG JAWAB WARGA NEGARA DI KELURAHAN RUMBIH - Indrawati, Cici; Pitoewas, Berchah; Adha, Muhammad a Mona (JURNAL PEKAN : Jurnal Pendidikan Kewarganegaraan, 2022)
The influence of awareness of ownership of motorized vehicle certificates is important for the community as a form of citizen responsibility in terms of obeying state rules. Therefore, this study was conducted with the aim of knowing the effect of awareness of the completeness of ownership of motorized vehicle registration certificates in the rumbih village. The research method used is a quantitative approach with descriptive methods, then data collection techniques in the field are carried out by means of observation and questionnaires. . Responsibility to the community which includes the rules, norms that apply in the community. Then the responsibility for religion which includes God related to religion and beliefs. With regard to a sense of responsibility, humans should base the assumptions of each individual by acknowledging the fact that humans in narrow and broad relationships need each other to realize the values of life that are felt to be good and support the existence of each individual. Based on the results and discussion, a regression model has been obtained with an r-square of 7.8% which has fulfilled all the classical assumptions in linear regression. In addition, based on the hypothesis test that has been carried out, it can be concluded that the completeness of ownership of a motorized vehicle registration certificate significantly affects aspects of citizen responsibility. Based on the sign of the regression, it indicates that ownership of a motorized vehicle registration certificate has a positive effect on aspects of citizen responsibility.Keywords: Public Awareness, Citizens, ResponsibilitiesÂ Â